2020
DOI: 10.1186/s12870-020-02372-w
|View full text |Cite
|
Sign up to set email alerts
|

Flowering in Persian walnut: patterns of gene expression during flower development

Abstract: Background: Flower development and sufficient fruit set are important parameters with respect to walnut yield. Knowledge about flowering genes of fruit trees can help to conduct better molecular breeding programs. Therefore, this study was carried out to investigate the expression pattern of some flowering genes (FT, SOC1, CAL, LFY and TFL1) in Persian walnut (cv. Chandler) during the growing season and winter dormancy. Results: The results showed that walnut flower induction and initiation in Shahmirzad, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Currently, in walnut varieties, very little is known about the signals that underlie the transition between the juvenile and adult phases. Recent studies have identified flowering-related genes associated with this transition in walnut trees [21,22]. Remarkably, transcriptome profiling (RNA-seq) has revealed thirty-one DEGs associated with this floral transition in J. regia [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in walnut varieties, very little is known about the signals that underlie the transition between the juvenile and adult phases. Recent studies have identified flowering-related genes associated with this transition in walnut trees [21,22]. Remarkably, transcriptome profiling (RNA-seq) has revealed thirty-one DEGs associated with this floral transition in J. regia [22].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other plants, the mechanism of floral transition in walnut remains less studied. Using RNA sequencing (RNA-Seq) analyses, recent studies have proposed several candidate genes associated with the juvenile-adult phase change in walnut trees [21,22], but the critical genes regulating the precocious characteristic of EF walnut germplasm are still unknown. A high-quality chromosome-scale reference genome was recently released for the walnut [23].…”
Section: Introductionmentioning
confidence: 99%
“…De novo transcriptomes assemblies can be developed for the studies in functional genomics of plants. Mohammad Sadat-Hosseini [ 38 ] compared the assembled transcripts with transcripts of the walnut leaf, published genome assembly for the ‘Chandler’ cultivar using the BLAST algorithm and identified a number of novel homologue transcripts. This is a combine study of the full-length transcriptome sequences and transcriptome analysis to conduct the transcript detection of flower buds in walnut.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, some cold-induced genes are enriched in the responses to abiotic stresses; some cold-repressed genes are enriched in the regulation of transcription, and response to hormone stimulus [ 16 , 38 , 41 , 54 ]. In addition, some flowering genes, including FLOWERING LOCUS T ( FT ) and SUPPRESSOR OF OVEREXPRESSION OF CO 1 ( SOC1 ), are increased by cold to control flower development [ 21 , 39 ], indicating that some developmental genes function in cold response to balance the developmental processes under cold condition by interacting with cold-responsive genes.…”
Section: Introductionmentioning
confidence: 99%